The pattern of local utilization and trade in wildlife /trophies in Saki West Local government area, Oyo State, Nigeria (2021)
Wildlife species and trophies are of valuable use to humanity. These values include aesthetic, education, medicinal purpose, recreation, and as foreign exchange earner. Legitimate hunters and poachers alike are the main source of supply of wildlife species and trophies whilst vendors market them. This study is purposed to indicate the pattern of utilization of wildlife species in the study area. Fifteen sampled communities were surveyed in the study area. A hundred respondents were served with a copy of each of the questionnaires. The questionnaire sought information on the following variables namely, socio-economic characteristics of the respondents, source, and types of the species, and commercial dynamics of the trade. The Data collected were analyzed applying statistical tests including the t-test to determine the frequency distribution on the benefit-cost ratio and profitability index. The result revealed that the economic returns on both the wildlife species and trophies trade are profitable with a BCR (Benefit-cost ratio) of 5.00% (P = ≤ 0.05) and 2.92% respectively. This fact shows that wildlife species and trophies contribute significantly to the economics of the area. Conservation education and awareness should be encouraged against poaching and wild-scale domestication practices should be engaged in to reduce or even eliminate poaching activities on the wildlife species concerned. These measures should adequately supplement the animal protein level of traditional livestock and enhance sustainable food security globally.